Metamorphoses of the Gold Bug: Soviet Illustrations for Edgar Poe's Prose - Nina A. Moroz (Литература двух Америк)
The paper deals with illustrations for Edgar Allan Poe’s short stories, created by Soviet artists of different generations and published in different decades, from the New Economic Policy period to perestroika. Our main focus are the illustrations of Dmitri Mitrokhin, Alexandr Silin, Nikolai Kuzmin, Vladimir Noskov and Sergey Sokolov. Our aim was not only to describe unique personal style of each artist or to analyze the complex relationship between the illustrations and Poe’s text, but also to put the illustrations in historical and cultural context, find their correlation with the publishers’ preferences, market or censorship requirements, and, in general, the idea of Poe’s place in a Soviet library. Poe’s “tales of ratiocination”, in particular “The Gold Bug”, used to be the main object of Soviet illustrators’ interest for a long period of time. Interestingly enough, they avoid plain entertaining position and take various approaches, e.g. exoticism in Mitrokhin’s landscapes, Kuzmin’s representation of transience of life, or references to film aesthetics in Sokolov’s illustrations. Poe’s Gothic tales were rarely illustrated in USSR. Alexandr Silin’s illustrations of the 1920s were strongly influenced by British book design of the previous decades. Vladimir Noskov created his metaphorical illustrations for a Soviet book series “Library of World Literature” (“Biblioteka vsemirnoi literatury”, 1976). Soviet illustrated editions of Poe’s prose in 1960–1970s reflect his status of a canonizes “classic” author for both adult and young adult readers. Especially important are the illustrations in various book series, from prestigious “Library of World Literature” to popular “World of Adventures” (“Mir priklucheniy”).